2022
DOI: 10.1111/1754-9485.13348
|View full text |Cite
|
Sign up to set email alerts
|

Quality management in radiotherapy treatment delivery

Abstract: Radiation Oncology continues to rely on accurate delivery of radiation, in particular where patients can benefit from more modulated and hypofractioned treatments that can deliver higher dose to the target while optimising dose to normal structures. These deliveries are more complex, and the treatment units are more computerised, leading to a re-evaluation of quality assurance (QA) to test a larger range of options with more stringent criteria without becoming too time and resource consuming. This review explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 86 publications
(136 reference statements)
0
15
0
Order By: Relevance
“…If a plan is too complex, not modelled precisely, or utilises beam arrangements that are not robust to changes in patient anatomy or other parameters, then the delivered dose will not match the initial clinically accepted treatment plan. The issue of delivering the planned dose accurately is a separate, but intrinsically inter‐linked topic 95 . However, some points are worth mentioning.…”
Section: Treatment Plan Evaluation Methods and Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…If a plan is too complex, not modelled precisely, or utilises beam arrangements that are not robust to changes in patient anatomy or other parameters, then the delivered dose will not match the initial clinically accepted treatment plan. The issue of delivering the planned dose accurately is a separate, but intrinsically inter‐linked topic 95 . However, some points are worth mentioning.…”
Section: Treatment Plan Evaluation Methods and Toolsmentioning
confidence: 99%
“…The issue of delivering the planned dose accurately is a separate, but intrinsically inter-linked topic. 95 However, some points are worth mentioning.…”
Section: Treatment Plan Reportingmentioning
confidence: 99%
“…Radiotherapy (RT) is one of the main treatment modalities for neoplastic lesions. The goal of RT is to deliver a prescribed radiation dose (which is the energy deposited in matter by ionizing radiation per unit mass) to a tumor site meanwhile minimizing the damage to healthy tissue . The validation and radiation process control depends on the measurement of the absorbed dose, usually obtained with the use of dosimetric systems.…”
Section: Introductionmentioning
confidence: 99%
“…In this step, the patient's treatment is conducted as a dry run before the patient's actual treatment. This process is performed with the help of computers to simulate the patient's anatomy and cancer location, for both practice and quality assurance purposes [11]. A study conducted in 2018 confirmed that this process resulted in reduction in the rate of incidents during treatment and anxiety levels of both patients and staff during treatment [12].…”
Section: The Radiotherapy Chainmentioning
confidence: 99%